A new species in the Genus Bromus - Sales, Fatima; Smith, Philip (Edinburgh Journal of Botany, 2010)
The material here named Bromus lusitanicus Sales & P. M. Smith, sp. nov. (Gramineae) was discovered and collected during 1982-83 at Souzelas near Coimbra (central Portugal). It shows marked affinities to B. racemosus L. and B. pseudosecalinus P. M. Smith. These species form a complex of annuals which have 3-veined lower glumes, 5-veined upper glumes, subterete spikelets, margins of lemma more or less inrolled in fruit, and the awn terete, straight or curved, arising just below the apex of the lemma, although sometimes absent.